Evaluation of skin beetles (Coleoptera: Dermestidae) as model organisms for nutritional bioavailability studies of companion animal foods - Toth, Mollie Margaret (Kansas State University, 2024)
It has been shown over recent years that pet owners are becoming more aware of the influence that their pet’s nutrition can play on the pet’s life expectancy, wellness, and energy. Consequently, pet owners have been pushing these values onto the pet food industry, influencing the formulations of diets to incorporate novel ingredients, with better balanced nutrition, and more fortified for specific medical conditions or ages. All pet food companies must follow the guidelines of the Association of American Feed Control Officials (AAFCO) as have been adopted by local authorities and in partnership are enforced by the United States Food and Drug Administration (FDA) to certify the safety of food products, supplements, and veterinary products. The FDA’s Federal Food, Drug, and Cosmetic Act ensures proper manufacturing, safety, and labeling of companion animal feeds. With more companies targeting pet owners with scientific claims for health benefits, more research is being conducted for pet foods that must be overseen by the Institutional Animal Care and Use Committee (IACUC) when taking place in university laboratories. But with the many restrictions implemented by IACUC, it has been difficult to fulfill these research demands. However, IACUC only places emphasis on research conducted using vertebrates or cephalopods, creating an opportunity for insects to become potential model organisms for pet food research. As a result, in the first study, three different species of beetles (Coleoptera: Dermestidae) were investigated in this research: Trogoderma variabile (Ballion), Trogoderma inclusum (LeConte), and Dermestes maculatus (DeGeer). The larvae of all three species were fed a balanced pet food diet to determine their protein efficiency ratios (PERs) and either placed in an incubator or a countertop for six days. The results demonstrated that D. maculatus larvae were the most efficient at converting ingested protein into body weight gain when placed in the incubator, with an average PER value of 1.439. Unfortunately, the molting of some larvae interfered with the body weights recorded before and after feeding. A second experiment was conducted using only D. maculatus larvae with a shorter time window of two days to prevent the time necessary to molt. Although there were fewer moltings, they still occurred, so another time window of 24 hours was tested and was found to be successful in preventing the larvae from molting and yielding an improved average PER value of 2.476. In the second study, experiments were implemented to determine if D. maculatus larvae could detect the quality of different protein sources in prepared companion animal diets through the standard PER assessment. Seven different diets were tested, including a commercially available balanced pet food diet, one lacking protein (negative control), spray dried egg (a positive control known to have balanced amino acids for mammal companion animals), soy protein concentrate, corn gluten meal, fish meal, and pea protein concentrate. The highest average PER recorded came from the spray dried egg diet at 6.455, followed by fishmeal at 6.238. The two diets were not significantly different in ranking, possibly attributed to fish being a known food of choice for D. maculatus. The next highest PER values were soy protein concentrate > pea protein concentrate > balanced pet food diet, corn gluten meal > no protein. These results are supported by the general amino acid makeup of the ingredients, all known to have a different limiting amino acid and protein quality. The results of both studies have shown similar outcomes to previous PER studies of companion animal feeds, suggesting that D. maculatus has potential as a model organism for pet food nutritional bioavailability studies in the future. Future experiments needed to support these findings would be to test prepared diets at various protein percentages, 0%, 5%, 10%, 15%, and 20%, to demonstrate the larvae’s efficiency at utilizing the protein sources for growth, resulting in higher PERs from higher protein percentage diets. Further studies should be conducted in determining the beetles’ essential amino acid profiles to verify that they are similar in order of limiting factor to those of the companion animals that they would model for.
Keywords: Protein quality; PER; Dermestid beetles; Protein efficiency ratio; Companion animal; Pet food